User Interface Design Information On Traditional Games In East Kotawaringin Using Ucd Method - Eki Juliana; Minarni (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This research aims to design the user interface of the Android application "BorneoTraditional Games" which introduces and preserves the traditional games of East Kotawaringin through the user-centered design method. The user-centered design method used includes Plan The Human Centered Design, Specify the Context of Use, Specify User and Organizational Requirements, Produce Design Solutions, and Evaluate Design Against User Requirements. The traditional games explained include balogo, bagasing, sepak sawut, manyipet, batukupan, and egrang. The user interface design is created using the Figma application and evaluated using the cognitive walkthrough method that refers to exploratory learning. The goal of this application is to introduce and preserve the unique culture of Central Kalimantan as traditional games are being eroded by electronic games. This design is created to be accessible and usable by various groups and to attract tourists through the information provided and a unique design that is characteristic of the local area. The user interface display created includes a Splashscreen, Dashboard containing the latest recommended information, a search menu containing a list of traditional games from East Kotawaringin and a detailed information page of traditional games complete with photos and videos. The results of usability testing using the cognitive walkthrough method showed good user satisfaction. Through usability testing, the researcher could identify problems experienced by users and provide improvement recommendations. The next development needs to create a more comprehensive testing procedure and involve various techniques as well as expanding the scope of participants. Subsequent research can also pay attention to ISO standards in user interface testing to ensure product safety and quality and provide optimal user experience.